Strategi mengurangi emisi gas rumah kaca untuk mengatasi konflik global akibat perubahan iklim - Ifemona Sarofamati Daeli (Environment Conflict, 2024)
Background: Greenhouse gas (GHG) emissions, such as methane and CO₂, are major contributors to global temperature rise as they trap heat from the sun that would otherwise reflect out of Earth’s atmosphere, leading to global warming. The impacts of these emissions include sea level rise, climate change, and disruptions to economic, social, educational, and food security sectors. Human activities, particularly in industry, livestock, agriculture, transportation, and waste management, significantly contribute to carbon emissions, making mitigation and adaptation measures essential. Method: This study employs a literature review, gathering data from scientific articles, news sources, international agreements, and other publications to understand the impacts of GHG and response strategies. Findings: Identified mitigation solutions include shifts to renewable energy, improvements in energy efficiency, and enhanced waste management. Adaptation efforts, such as climate-resilient infrastructure and sustainable agricultural practices, have also been implemented. However, challenges remain in local implementation and funding gaps. Conclusion: The study concludes that successful GHG reduction and climate change management require a synergy between mitigation and adaptation. International and cross-sectoral collaboration is crucial for long-term environmental sustainability. Novelty/Originality of this article: This article provides an in-depth analysis of the synergy between mitigation and adaptation efforts at various levels, identifies implementation challenges, and presents opportunities for innovative collaborative strategies not widely discussed in previous studies.